Retinoic Acid, Leaky Gut, and Autoimmune Diseases - Leila Abdelhamid (Nutrients, 2018)
A leaky gut has been observed in a number of autoimmune diseases including type 1 diabetes, multiple sclerosis, inflammatory bowel disease, and systemic lupus erythematosus. Previous studies from our laboratory have shown that lupus mice also bear a leaky gut and that the intestinal barrier function can be enhanced by gut colonization of probiotics such as Lactobacillus spp. Retinoic acid (RA) can increase the relative abundance of Lactobacillus spp. in the gut. Interestingly, RA has also been shown to strengthen the barrier function of epithelial cells in vitro and in the absence of probiotic bacteria. These reports bring up an interesting question of whether RA exerts protective effects on the intestinal barrier directly or through regulating the microbiota colonization. In this review, we will discuss the roles of RA in immunomodulation, recent literature on the involvement of a leaky gut in different autoimmune diseases, and how RA shapes the outcomes of these diseases.